Acts 8.9–25 and Witchcraft Manipulations in Nigerian Christianity - Ukeachusim, Chidinma P. (2024)
In Nigeria, witchcraft is operated under the banner of indigenous religions, Islam, and Christianity. It is a biblical theological concern for witchcraft to be practiced under the banner of Christianity. This article aims to exegetically explore, interpret, and apply the context of Acts 8.9–25 to the syncretic practices of some acclaimed plenipotentiaries of God, and some lay Christians in Nigeria who synchronize their Christian faith with witchery as Simon attempted to do in the first century era. Redaction-critical method is used to unveil the theological motif and implications of the manipulative practices of Simon as a superficial follower of Jesus in Acts 8.9–25, and the subtle ways witchcraft manipulation are being blended with Christianity in Nigeria. This study argues that Christians identifying with witchery is a rebellious sin that requires them to repent or perish as Peter instructed Simon.
Keywords: Nigerian Christianity; mission mandate; lay Christians; plenipotentiaries of God; manipulations; Sorcery; Witchcraft; Acts of the Apostles